0597 The Findings Of Narcolepsy On Tc-99m ECD Brain Perfusion SPECT As Analyzed By Easy Z-Score Imaging System. (12th April 2019) - Lin, Wei; Wei, Cheng Yu; Matsuda, Hiroshi; Hung, Guang Uei
Abstract: Introduction: Type 1 narcolepsy (T1N) is a disorder characterized by hypersomnolence, cataplexy, sleep paralysis or sleep-related hallucination. Cataplexy is a sudden loss of muscle tone triggered by emotional changes such as laughing and is caused by the inappropriate activation of descending neural pathways that promote atonia. Type II narcolepsy (T2N) is a disorder like T1N but without cataplexy. It has been established that HLA-DQB1*0602 is a marker for narcolepsy on chromosome 6 across all ethnic groups. For patients with narcolepsy, the pattern of hypoperfusion on brain SPECT had been controversial on previous studies. Methods: In this report, we demonstrated the imaging findings of narcolepsy cases with free of all drugs on Tc-99m ECD brain perfusion SPECT, which were firstly analyzed by the easy Z-score imaging system (eZIS) among the published literature. eZIS is a computer-assisted statistical analysis based on the comparison with age-classified ECD normal database. eZIS provides objective and reproducible interpretation of SPECT images and has been widely utilized in Japan. Results: All cases consistently showed hypoperfusion in bilateral anterior to posterior cingulate gyrus. SPECT in early Alzheimer disease was hypoperfusion over medial temporal and posterior cingulate gyrus, compatible with the hypoperfusion area at our subjects. This result suggests that SPECT examinations by eZIS analysis clearly showed obvious hypoperfusion of the limbic system in narcolepsy. Conclusion: This result suggests that SPECT examinations by eZIS analysis clearly showed obvious hypoperfusion of the limbic system in narcolepsy patient. Support (If Any): N/A